The political impact of refugees in Africa - Demir, Cansu; Mayda, Anna Maria; Maystadt, Jean-François (CGIAR System Organization, 2025)
The political impact of refugees is largely unknown in low-income countries, although these destinations host the majority of forcibly displaced people, and more specifically refugees. We exploit yearly variation in the number of refugees in refugee camps and election data at the sub-national level in 16 African countries in 2000-2016. The estimates show that the arrival of refugees increases local support to the national incumbent and reduces political competition, but only when hosting countries implement inclusive policies towards refugees. Inclusive policies play a crucial role also when we estimate the impact of refugees on individual-level satisfaction with the government and with provision of local public goods (education, health care and infrastructure), in the Afrobarometer, and on local economic activity, using night light data.